Environmental economics and policy making in developing countries current issues - Seroa da Motta, Ronaldo; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
The authors provide a comprehensive analysis of topics varying from the general problems of growth and conservation to specific applications such as; pollution costs, environmental taxation, deforestation and climate change. This volume also offers policymakers a comprehensive view of the challenges they face, and the legacies they leave, in order to convert environmental policy making into an actual programme of welfare improvement.
1. Economic growth, the environment and welfare : are they compatible? -- 2. The impact of perverse subsidies on international trade and the environment -- 3. Valuing statistical lives -- 4. The valuation of health impacts in developing countries -- 5. Economic instruments for waste management in Brazil -- 6. Deforestation, land degradation and rural poverty in Latin America : examining the evidence -- 7. Public policies and deforestation in the Brazilian Amazon -- 8. Technology, climate change, productivity and land use in Brazilian agriculture -- 9. Economic incentives and forest concessions in Brazil.
Includes bibliographical references and index.
Keywords: Environmental economics -- Developing countries; Developing countries -- Economic policy; Electronic books